Rapid mapping of Escherichia coli::Tn5 insertion mutations by REP-Tn5 PCR. - Subramanian, P S; Versalovic, J; McCabe, E R; Lupski, J R

(untitled) (Genome Research, 1992)
We describe a novel method to map chromosomal Escherichia coli::Tn5 insertion mutations rapidly. This method utilizes the ends of Tn5 and the E. coli REP sequence as primer binding sites for the polymerase chain reaction (PCR). The unique E. coli chromosomal sequence located between these primer binding sites is amplified by PCR and used as a probe to identify the recombinant clones from the Kohara phage ordered E. coli miniset bank that contains the Tn5 mutated loci. We used this approach to map two Tn5 insertion mutations previously identified by their effect on glycerol metabolism. The insertion mutations mapped to glpD, the aerobic sn-glycerol-3-phosphate dehydrogenase gene. Phenotypic analysis of the mutant strains revealed one with partial GlpD activity, suggesting transposon-mediated alteration of promoter activity. This mapping method should be applicable to the rapid physical mapping of any insertion mutation in the E. coli chromosome.